(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study can analyse customer satisfaction various risks faced by electronic banking customers in the Kanyakumari district. The study also focused on various factors that determine customer satisfaction like demographic factors, employee behaviour, banking services offered to customers, types of accounts holding, and transactions preferred in electronic banking.